PENGARUH MODEL PEMBELAJARAN PROBLEM BASED LEARNING TERHADAP AKTIVITAS BELAJAR SISWA KELAS V SDN TEMBOK DUKUH III SURABAYA - Nayla Zulfia; Prastyo, Danang (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The purpose of this study is to determine the effect of the PBL model on the learning activities of fifth-gradestudents at SDN Tembok Dukuh III Surabaya. This research is experimental in nature. The sampleconsists of students from classes V-A and V-B, while the population consists of all fifth-grade students at SDN Tembok Dukuh III Surabaya. The Postest OnlyNonequivalent Control Group Design is the quasi-experimental design used in this study. SPSS software was used to analyze the data. Data analysis showsthat the PBL model has an impact on the learningactivities of fifth-grade students at SDN Tembok Dukuh III Surabaya.